THE IMPORTANCE OF DEVELOPING PHYSICAL QUALITIES IN THE SPORT OF VOLLEYBALL - Akimov No’kisbay Tengelbaevich; Jaksimova Gulmira Adilovna (Web of Journals Publishing, 2025)
This scientific article explores the importance and methods of developing the physical qualities of volleyball players. Physical fitness is a key factor in achieving success in volleyball, requiring the enhancement of physical traits such as speed, endurance, strength, and coordination. The article analyzes various training methods, exercises, and their effectiveness in volleyball. It also examines specialized training aimed at improving muscle strength, flexibility, and overall physical condition, as well as their impact on players' technical and tactical skills.
Keywords: Volleyball, physical qualities, training, strength, speed, endurance, coordination, fitness, player, muscle strength, flexibility.